“The Prince of Landscape Painters” in Russia: New Data on the Works of B. C. Koekkoek in Imperial and Private Collections - Kostyria, Maksim A. (Actual Problems of Theory and History of Art, 2022)
The article provides new information on the collecting of paintings by B. C. Koekkoek in the Russian Empire and their fate. Barend Cornelis Koekkoek (1803–1862) was the greatest master of the romantic landscape in the Netherlands. Contemporaries called him “The Рrince of Landscape Painters”, his works had phenomenal success. B. C. Koekkoek was elected an honorary member of several European Academies of Arts (including St. Petersburg Imperial Academy of Arts). However, soon after his death the master was forgotten. For many years B. C. Koekkoek was known only to a narrow circle of specialists. Only in the second half of the 20th century the name of the painter returned from historical non-existence.The first acquaintance of the Russians with the work of B. C. Koekkoek took place in 1839, when being in The Hague, Cesarevich Alexander Nikolayevich ordered B. C. Koekkoek one of the largest paintings in the painter’s oeuvre. The picture was in the collection of the Imperial family until 1917, and then it ended up abroad. For many years, the canvas was considered lost. But its story has not ended: the landscape by B. C. Koekkoek was discovered by the author of the article in the Novokuznetsk Art Museum. We also managed to clarify the history of the other paintings by B. C. Koekkoek from the collections of members of the Imperial family and Russian aristocrats: for example, from the collections of Grand Duchess Maria Nikolaevna and Dmitry Petrovich Botkin. The fate of these paintings was unknown to art historians, including Friedrich Gorissen — author of B. C. Koekkoek’s catalogue raisonne.In addition, the article attempts the reconstruction of the history of “Landscape with a Herd” (1847, State Tretyakov Gallery, Moscow) by Mikhail Spiridonovich Erassi (1823–1898), a copy of the landscape by B. C. Koekkoek from the Russian private collection.
Keywords: 19th century; B. C. Koekkoek; art collecting; Russian Empire; The Netherlands; landscape; painting